Bluebasin, Trinidad - (:unkn) unknown (Thomas Studio, [Trinidad and Tobago]; Printed in Saxony, 2011)
The postcard shows the magnificent Blue Basin Waterfall located in Diego Martin, a town in northwest Trinidad.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Diego Martin; Waterfalls--Trinidad and Tobago; Blue Basin Waterfall (Trinidad and Tobago)